A Mandated Basis of Interorganizational Relations: The Legal-Political Network - Joseph A. Raelin (Human Relations, 1980)
This paper seeks to broaden our understanding of interorganizational phenomena by focusing on the mandated basis of interorganizational relations, which is distinguished from the exchange and power-dependency bases. In particular, the paper defines and elaborates upon a subset of mandated interorganizational relations-the legal-political network. Five characteristics of the legal-political subset are identified based upon the author's prior empirical research. Avenues for future research are cited.
Keywords: D85; L14; M10; 330; Interorganizational relations; Mandated social networks; Legal-political networks